(Poly)phenols and cardiovascular diseases: Looking in to move forward. (August 2020) - Vetrani, Claudia; Costabile, Giuseppina; Vitale, Marilena; Giacco, Rosalba
Graphical abstract: Highlights: (Poly)phenol intake associates with cardiovascular health. Controversial evidence from human trials is linked to methodological limitations. (Poly)phenols might have selective effects on gut microbiota composition. A comprehensive approach is needed to deeply understand the effects of (poly)phenols. Abstract: Dietary (poly)phenol intake has been associated with a lower risk of cardiovascular mortality and new events. However, no conclusive data can be drawn from clinical trials evaluating the effects of (poly)phenols on cardiovascular risk factors. In addition, the mechanisms of action behind the beneficial association of (poly)phenol intake with cardiovascular health are not completely understood. Therefore, this perspective aimed to highlight the main methodological limitations that might explain the conflicting results obtained so far. In addition, novel insights on local and systemic effects of (poly)phenols were discussed. Finally, some critical issues to take into consideration in future studies were reported. This more comprehensive approach could represent a strategy to deeply understand the effects of (poly)phenols on human health.